Financial Sanctions Effectiveness as a Foreign Policy Tool on Crises Management - Psomopoulou, Katerina (HAPSc Policy Briefs Series, 2021)
Post-Cold War financial sanctions utilization reached its peak as policymakers employed used them in order to face address major international crises. Their prominence among foreign policy instruments sparked the interest of many scholars and enriched the existing literature. However, their attractiveness raises several interesting research questions, such as "Do targeted sanctions suffice to achieve the defined objectives?", "Which variables affect their effectiveness?", "What shortcomings can be overcomed to make them more productive?" To probe these queries, in this paper different aspects of both comprehensive and financial/ smart/ targeted sanctions are examined. It is concluded that political will and better understanding of their effects is needed to improve sanctions design and overcome legal and administrative obstacles, since the current flaws are not incurable.